Amendments to my article "THE EKATERINBURG SEMINAR "ALGEBRAIC SYSTEMS'': 50 YEARS OF ACTIVITIES" - Lev N. Shevrin (Ural Mathematical Journal)
Amendments to my article "THE EKATERINBURG SEMINAR "ALGEBRAIC SYSTEMS'': 50 YEARS OF ACTIVITIES"